Consumer buying behavior of luxury branded good / Darel Nicol Luna Agam … [et al.] - Agam, Darel Nicol Luna; Usin @ Husin, Ymma Fatzrin (2013)
Consumers make many buying decisions every day decisions are the focal point of a marketer's effort. Marketing stimuli consist of four Ps, which are product, price, place, and promotion. Consumer purchases are strongly influenced by cultural, social, personal, and psychological characteristics (Azuma & Fernie, 2003). The luxury sector targets its products and services at consumers at the top-end of the wealth spectrum (Mansharamani & Khanna, 2008). These self-selected elites are more or less price-insensitive and choose to spend their time and money on objects that are plainly opulence rather than necessities (Mansharamani & Khanna, 2008). For these reasons, luxury and prestige brands have for centuries commanded an unwavering and often illogical customer loyalty.